2023
DOI: 10.2196/47094
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation Associated With Clinical-Grade Mobile App–Based Digital Therapeutic Interventions: Systematic Review

Abstract: Background Digital therapeutics (DTx), a class of software-based clinical interventions, are promising new technologies that can potentially prevent, manage, or treat a spectrum of medical disorders and diseases as well as deliver unprecedented portability for patients and scalability for health care providers. Their adoption and implementation were accelerated by the need for remote care during the COVID-19 pandemic, and awareness about their utility has rapidly grown among providers, payers, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Importantly, innovation and adoption are substantially different objectives, which require an expansive range of disciplines, policy advances and other factors to achieve the level of behavioural change needed to drive changes in practice at the clinical and user stages, not to mention the validated economics and value outcomes needed at the reimbursement and subsidy stages. [ 92 93 ]…”
Section: Technology Alone Cannot Change Healthcarementioning
confidence: 99%
“…Importantly, innovation and adoption are substantially different objectives, which require an expansive range of disciplines, policy advances and other factors to achieve the level of behavioural change needed to drive changes in practice at the clinical and user stages, not to mention the validated economics and value outcomes needed at the reimbursement and subsidy stages. [ 92 93 ]…”
Section: Technology Alone Cannot Change Healthcarementioning
confidence: 99%
“…However, portable medical devices for telemonitoring can cause inconvenience for the patient, for example, when they get in the way of daily activities or malfunctions occur that cannot be solved easily [ 30 ]. Multiple home rehabilitation devices are available and implemented; however, some technologies face limitations in the application, availability, as well as cost and preparation of appropriate rehabilitation therapist to support the rehabilitation process [ 31 ]. Arntz et al in [ 32 ] recently demonstrated that feasible and effective approaches are needed to implement functional home-based recovery, which meet patients’ demands and ensure adequate levels of treatment.…”
Section: Introductionmentioning
confidence: 99%